2015
DOI: 10.1016/j.ydbio.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin complex 1 (mTORC1) Is required for mouse spermatogonial differentiation in vivo

Abstract: Summary Spermatogonial stem cells (SSCs) must balance self-renewal with production of transit-amplifying progenitors that differentiate in response to retinoic acid (RA) before entering meiosis. This self-renewal vs. differentiation spermatogonial fate decision is critical for maintaining tissue homeostasis, as imbalances cause spermatogenesis defects that can lead to human testicular cancer or infertility. A great deal of effort has been exerted to understand how the SSC population is maintained. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 96 publications
(119 reference statements)
5
68
0
Order By: Relevance
“…Especially, inhibition of mTOR blocks translation initiation and cell cycle progression and, consequently, affects cell growth and proliferation by phosphorylating its targets p70S6K and 4EBP1 (Wang et al 2014a). The results from our previous in-vitro and present in-vivo studies revealed that NP exposure dephosphorylates p70S6K and 4EBP1, probably blocking protein synthesis, and therefore affecting testicular cell function and even spermatogenesis (Busada et al 2015;Duan et al 2016c). …”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Especially, inhibition of mTOR blocks translation initiation and cell cycle progression and, consequently, affects cell growth and proliferation by phosphorylating its targets p70S6K and 4EBP1 (Wang et al 2014a). The results from our previous in-vitro and present in-vivo studies revealed that NP exposure dephosphorylates p70S6K and 4EBP1, probably blocking protein synthesis, and therefore affecting testicular cell function and even spermatogenesis (Busada et al 2015;Duan et al 2016c). …”
Section: Discussionmentioning
confidence: 49%
“…It is well established that cellular autophagy is negatively regulated by mTOR and phosphorylation of mTOR at Ser2448 is an activator of mTORC1 (Yamamoto et al 2014). Moreover, mTOR regulates protein synthesis by phosphorylating downstream targets p70S6k and 4EBP1, at least partly controlling spermatogonial differentiation (Busada et al 2015;Churchward-Venne et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Our use of hypomorphic alleles enabled a genetic separation of the proliferative effects and differentiation requirements of PI3K and Tor in CySCs. Finally, there is evidence that PI3K/Tor activity promotes the differentiation of stem cells in gonads in mammals, suggesting that our findings might reflect a conserved role of Tor activity in promoting germ cell differentiation, both through autonomous and non-autonomous mechanisms involving somatic support cells (Adhikari et al, 2010;Busada et al, 2015;Hobbs et al, 2010;Reddy et al, 2008).…”
Section: Pi3k/tor Signaling and The Differentiation Of Stem Cellsmentioning
confidence: 75%
“…Retinoic acid stimulates translation of Kit mRNA in a manner dependent on PI3K, PDK1, AKT and mTOR signaling [48] (Fig. 2), whereas pharmacological inhibition of mTOR prevents retinoic acid-dependent spermatogonial differentiation and Kit translation [49]. Notably, RA exposure in this context has only a modest effect on transcriptional targets of RAR [25,48,49].…”
Section: Spermatogoniamentioning
confidence: 97%
“…2), whereas pharmacological inhibition of mTOR prevents retinoic acid-dependent spermatogonial differentiation and Kit translation [49]. Notably, RA exposure in this context has only a modest effect on transcriptional targets of RAR [25,48,49]. Rather, retinoic acid acts in a non-genomic manner (i.e., through PI3K signaling rather than direct activation of transcription by RAR) to induce Kit expression in differentiating spermatogonia [50].…”
Section: Spermatogoniamentioning
confidence: 99%